Cryogenic magnetic properties and magnetocaloric performance in double perovskite Pr2NiMnO6 and Pr2CoMnO6 compounds. Issue 17 (1st December 2018) - Zhang, Yikun; Li, Huadong; Dan Guo; Hou, Long; Li, Xi; Ren, Zhongming; Wilde, Gerhard
Abstract: Double perovskite Pr2 NiMnO6 (PNMO) and Pr2 CoMnO6 (PCMO) ceramics have been synthesized and their crystal structure, microstructure, as well as cryogenic magnetic properties and magnetocaloric performance have been investigated. The crystal structure of PNMO and PCMO ceramics was determined to be monoclinic with space group of P21/n at room temperature. A ferromagnetic to paramagnetic (FM-PM) phase transition (second-order) occurred in PNMO and PCMO around 208 and 170 K, respectively. Significant reversible magnetocaloric effect (MCE) was found and the values of the maximum magnetic entropy change (-Δ S M max ) were 3.15 and 3.91 J/kg-K under the magnetic field change (Δ H ) of 0–7 T in PNMO and PCMO, respectively. The corresponding relative cooling power ( RCP ) values were 241.9 and 229.9 J/kg.